The Prevent Duty in Education Impact, Enactment and Implications - Busher, Joel; Jerome, Lee (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
"This invaluable book brings empirical rigour to a debate that is too often emotive, polarised and selective in its approach to the facts. By examining how the Prevent duty is enacted in practice, the authors provide a sound evidence base for future policy development." -David Anderson QC, House of Lords, and former Independent Reviewer of Terrorism Legislation "This book is crucial reading for at least three audiences: first, policy makers who are revising counter-terror and Prevent type strategies, second, those making judgements on Prevent enactment such as OFSTED, and third, those involved in training around extremism and radicalisation in schools. The book reveals what teachers and students actually want to know in this contested and complex area. It is an impressive read." -Lynn Davies, Birmingham University, UK and Director of ConnectFutures This open access book explores the enactment, impact and implications of the Prevent Duty across a range of educational contexts. In July 2015 the UK became the first country to place a specific legal requirement on those working in education to contribute to efforts to 'prevent people from being drawn into terrorism'. Drawing on extensive research with staff, children and young people, the editors and contributors provide new insight into how this high-profile - and highly contentious - policy has shaped educational practice in Britain today. It will be a valuable resource for researchers, policymakers and others interested in the design, implementation and on-the-ground effects of Prevent or similar programmes internationally that place education at the heart of efforts to prevent or counter violent extremism. Joel Busher is Associate Professor at the Centre for Trust, Peace and Social Relations at Coventry University, UK. Lee Jerome is Associate Professor of Education at Middlesex University, UK.